THE EFFECTS OF CHANGING MEMBRANE COMPOSITIONS AND INTERNAL ELECTROLYTES ON THE RESPON OF POTASSIUM ION SENSOR - Ulianas, Alizar; Heng, Lee Yook (Sainstek : Jurnal Sains dan Teknologi, 2015)
A study on the changing of membrane compositions and internal solution towards the response potassium ion sensor was carried out. Potassium ion sensor based on photocured cross linking poly(n-butyl acrylate) membranes with varying composition of valinomycin (val), sodium tetrakis [3.5-bis(trifluoro-methyl) phenyl] borat (NaTFPB), types ion of internal solution were investigated. Effects of varying composition of val, NaTFPB, types and concentration of internal solution were observed on potassium ion sensor. The effect of higher val composition was lower LOD, wider linear range, lower sensitivity but increase selectivity. Higher NaTFPB compositions lead to lower LOD, higher sensitivity and selectivity. The effect of changing internal electrolyte lead to lower LOD, wider linear response range and higher selectivity according to internal electrolyte consisting Na+, Ca2+ and K+, and sensitivity increase following internal electrolyte with Ca2+, K+ and Na+.Key words: ion sensor, ion selective membrane, ionofor, lipofilik salt